2021
DOI: 10.3390/cancers13174321
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-DOTATATE PET/CT and MRI with Diffusion-Weighted Imaging (DWI) in Short- and Long-Term Assessment of Tumor Response of Neuroendocrine Liver Metastases (NELM) Following Transarterial Radioembolization (TARE)

Abstract: The aim of this study was to evaluate the role of SUV and ADC in assessing early response in patients with NELM following TARE. Thirty-two patients with pre- and postinterventional MRI with DWI and 68Ga-DOTATATE PET/CT were included. ADC and SUV of three target lesions and of tumor-free spleen and liver tissue were determined on baseline and first follow-up imaging, and tumor to spleen (T/S) and tumor to liver (T/L) ratios were calculated. Response was assessed by RECIST 1.1 and mRECIST on first follow-up, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
0
0
2
Order By: Relevance
“…32,33 Additionally, in a different study, the change of T/S and T/L ratios on the first follow-up was identified as the best metric to correlate with longer hepatic PFS in NET patients undergoing TARE. 34 The main limitation of this study was its small sample size, which is related to the low incidence of NETs and everolimus representing a second-line treatment. Additionally, the retrospective analysis represents a limiting factor, as time intervals between PET/CT scans and everolimus treatment were heterogeneous, and prior therapies differed among patients.…”
Section: Discussionmentioning
confidence: 96%
“…32,33 Additionally, in a different study, the change of T/S and T/L ratios on the first follow-up was identified as the best metric to correlate with longer hepatic PFS in NET patients undergoing TARE. 34 The main limitation of this study was its small sample size, which is related to the low incidence of NETs and everolimus representing a second-line treatment. Additionally, the retrospective analysis represents a limiting factor, as time intervals between PET/CT scans and everolimus treatment were heterogeneous, and prior therapies differed among patients.…”
Section: Discussionmentioning
confidence: 96%
“…Gastrointestinale NET erscheinen hypointens in T1, hyperintens in T2 und zeigen eine KM-Aufnahme sowie eine Diffusionsrestriktion in diffusionsgewichteten Sequenzen. Die DWI eignet sich zudem zur Beurteilung therapieassoziierter Veränderungen nach transarterieller Chemoembolisation (TACE) oder selektiver interner Radiotherapie (SIRT) [31,32]. Bezüglich der Primärtumorlokalisation weist die MRT eine ähnliche Sensitivität und Spezifität wie die CT-Bildgebung auf [33,34].…”
Section: Tumortypunclassified
“…Gastrointestinale NET erscheinen hypointens in T1, hyperintens in T2, zeigen eine KM-Aufnahme und eine Diffusionsrestriktion in diffusionsgewichteten Sequenzen. Die DWI eignet sich zudem zur Beurteilung therapieassoziierter Veränderungen nach transarterieller Chemoembolisation (TACE) oder selektiver interner Radiotherapie (SIRT) [31,32]. Bezüglich der Primärtumorlokalisation weist die MRT eine ähnliche Sensitivität und Spezifität wie die CT-Bildgebung auf [33,34].…”
Section: Tumortypunclassified